A wireless Internet application for healthcare - Seshadri, K.; Liotta, L.; Gopal, R.; Liotta, T. (Proceedings 14th IEEE Symposium on Computer-Based Medical Systems. CBMS 2001, 2001)
The use of the Internet in daily healthcare business processes is still minimal compared to other industries. Healthcare information is inherently "mobile", i.e. it travels with the patient - and therefore, the need for information to be ubiquitously available is key to efficient and improved diagnostic accuracy, reliable care and reduced medical errors. This paper describes an elegant and intuitive wireless healthcare application for prescription writing and laboratory test review which leverages the Internet and significantly enhances the productivity of physicians, clinical laboratories and pharmacies, while at the same time saving patients time, improving accuracy in healthcare and providing an insight into future trends in healthcare applications.